2004
DOI: 10.1186/1471-2458-4-68
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of factors contributing to treatment adherence and knowledge of TB transmission among patients on TB treatment

Abstract: BackgroundThe treatment guidelines for tuberculosis treatment under Directly Observed Treatment, Short-course (DOTS) have been a common strategy for TB treatment in Zambia. The study was carried out in Ndola, Zambia, to investigate factors contributing to treatment non-adherence and knowledge of TB transmission among patients on TB treatment, in order to design a community-based intervention, that would promote compliance.MethodsA household-based survey was conducted in six randomly selected catchment areas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
150
5
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(188 citation statements)
references
References 13 publications
17
150
5
10
Order By: Relevance
“…In this study, contracting TB through sexual acts is likely to have been associated with the similarity of the disease and HIV/AIDS, which is widely known to be contracted through unprotected sexual acts. Similar findings regarding belief in TB transmission through sexual acts have been observed in a study in Zambia (Kaona et al, 2004).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this study, contracting TB through sexual acts is likely to have been associated with the similarity of the disease and HIV/AIDS, which is widely known to be contracted through unprotected sexual acts. Similar findings regarding belief in TB transmission through sexual acts have been observed in a study in Zambia (Kaona et al, 2004).…”
Section: Discussionsupporting
confidence: 75%
“…DOTS as a strategy, entails that medication is taken in the presence of the the care provider (WHO, 2002). Providing TB patients with drugs at distanced health facilities and later sending them to continue taking their treatment at home under supervision, poses serious challenges on compliance (Kaona et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…(11) In developing countries, the preoccupation with adherence to treatment has also motivated studies aimed at identifying the principal factors involved. (8,12,13) Socioeconomic aspects and obstacles to obtaining treatment, as well as limited understanding of the disease and of chemotherapy, were found to be common factors. In the present study, a more specific approach was not taken, due to the lack of such data on the medical charts.…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, various authors have attempted to define the incentives to adhere to treatment. (8)(9)(10) Among poor populations in the United States, financial and nonfinancial incentives have both been shown to improve adherence to the supervised treatment known as directly observed therapy, short-course (DOTS). (9) Another study conducted in the United States showed that the increasing number of benefits offered during treatment resulted in an inversely proportional decrease in treatment abandonment rates.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Apart from these, lack of financial sources, poor accessibility to health facilities and lack of knowledge about the symptoms, mode of spread and available treatment among the population affects the health seeking behaviour of patients and might promote delay in diagnosis, improper treatment, poor compliance to medications and development of drug resistance. 5,6 According to the World Health Organisation (WHO), TB is the leading infectious cause of death worldwide and there were 10.4 million TB cases and 1.7 million deaths in the year 2016. 7 Access to TB care has improved worldwide and TB mortality rate has shown 37% decline since 2000.…”
Section: Tuberculosis (Tb) Is An Infectious Disease Caused Bymentioning
confidence: 99%